MANAJEMEN PERILAKU PRO LINGKUNGAN PADA SANTRI PONDOK PESANTREN Al-QUR’AN TAZKIYAH INSANI DEPOK JAWA BARAT - Muhammad WRTI Tabtila; Akhmad Shunhaji; Susanto Susanto (CV. ADIBA AISHA AMIRA, 2023)
This study aims to analyze and describe the extent to which the ideal picture of the Tazkiyah Insani Al-Qur'an Islamic Boarding School is located in implementing pro-environmental behavior management for students at the Islamic boarding school. Qualitative research was conducted using a phenomonology approach. The data collection techniques used were primary and secondary data collection from observations, documentation, interviews conducted with seven respondents, and literature literature, which were then analyzed using data reduction techniques, data display, and data conclusions. The result of the research is pro-environmental behavior management at Tazkiyah Insani Al-Qur'an Islamic Boarding School has found the ideal position expected, starting from planning about clean and healthy living behavior, organizing the plan by involving all elements in the institution starting from building ventilation facilities, oxygen, light, sanitation, waste management, cleaning equipment, cleaning services and sanitation waste so that the management carried out meets the ideal description based on research ideas. In conclusion, pro-environmental behavior management is a facility expected by Islamic boarding schools to make students more aware of cleanliness and environmental care, so that the cleanliness of the Islamic boarding school environment is maintained to support the implementation of Al-Qur'an education in Islamic boarding schools.